2020
DOI: 10.1016/j.healthpol.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration, drift, distraction, and denial: How the politics of austerity challenges the resilience of prison health governance and delivery in England

Abstract: Highlights The impact of austerity on English prison health system remains under-theorised. Austerity decreases the resilience of prison health governance and broader enabling environment. Policy drift contributes towards sentencing proliferation and increased imprisonment of vulnerable populations. High turnover of justice ministers and privatisation impact coherent offender management. Preventive imprisonment and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Funding and provision of prison health services tends to be in the public sector. However, budget cuts resulting in reductions in staff and competitive pressure to contain costs, has seen an increase in privatization of prison care in some countries (Ismail, 2020). This has raised concerns about excessive cost reductions at the expense of quality of care, a lack of transparency and problems of oversite (Moore, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Funding and provision of prison health services tends to be in the public sector. However, budget cuts resulting in reductions in staff and competitive pressure to contain costs, has seen an increase in privatization of prison care in some countries (Ismail, 2020). This has raised concerns about excessive cost reductions at the expense of quality of care, a lack of transparency and problems of oversite (Moore, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental foundation of every healthcare service is its workforce but the current findings have demonstrated that the prison healthcare workforce is severely depleted. Prison healthcare provision in the UK is provided by a fragmentation of third-sector and for-profit companies, with healthcare staff employees often receiving terms and conditions that are viewed as inferior to those of their peers in the community 10 coupled with a lack of career development. Prison healthcare careers should be made more attractive with clear career trajectories, better terms and conditions, protected time for training, and investment in upskilling of current staff.…”
Section: Discussionmentioning
confidence: 99%
“…9 There is little research that focuses on the organisational factors influencing primary care in prisons and even less literature that pays attention to how these factors have an impact on quality and access. A notable exception are two papers by Ismail 8,10 that concentrate on macroeconomic conditions, governance structures, and the impact of austerity. Further, most prison healthcare studies tend to prioritise discrete areas of health such as communicable diseases, mental health, or drug treatment services to the exclusion of routine healthcare conditions encountered every day in primary care such as asthma, hypertension, or diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Early identification and support for SLCN and the positioning of this within L&D is not without its challenges. The criminal justice system and the NHS in England are both under a great deal of financial strain and there are competing needs for access to available resources (Ismail, 2020). Increased SLCN provision does carry an additional resource implication; however, the net economic gain in terms of ‘savings for health and social care services, improved quality of life, and productivity gains – exceed the costs’ (Marsh et al, 2010, p.5).…”
Section: Recognising Slcn Support In Police Custodymentioning
confidence: 99%